REDUCTION OF PLOT IN NOVEL IF BEALE STREET COULD TALK (1974) BY JAMES BALDWIN INTO FILM IF BEALE STREET COULD TALK (2018) BY BARRY JENKINS - Nanda Amelia Handaeni; Ika Yatmikasari; Yoga Sudarisman (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2022)
The objectives of this study are to (1) describe the ecranisation process in terms of plot reduction and (2) explain the function of the ecranisation process that appears in the plot of James Baldwin's novel If Beale Street Could Talk (1974) to the film If Beale Street Could Talk (2018) by Barry Jenkins. This study employs ecranisation theory by Eneste (1991) to analyze the transformation from novel into Film If Beale Street Could Talk. Descriptive qualitative data analysis was employed in this study. Data collecting methods based on a review of the literature because the medium utilized to create novels and films are different, the results of this study show that the ecranisation process happens in the plot. The reduction of plot from components that aren't as crucial for display causes a general reduction.